Supervisi Akademik Kepala Sekolah dalam Meningkatkan Motivasi dan Kinerja Guru: Sebuah Systematic Literature Review - Irra Julia Saputri (Journal of Innovation in Teaching and Instructional Media, 2026)
This study is a systematic literature review (SLR) of fifteen scientific articles from 2021 to 2025. This article aims to identify, evaluate, and synthesize previous research findings on the role of principals' academic supervision in improving teacher motivation and performance. Academic supervision is an important component in educational management that can contribute to teacher professional development and improve the quality of learning. Inclusion criteria include studies that discuss academic supervision by principals and its impact on teacher motivation and performance in the context of primary and secondary education. The results of the study indicate that effective academic supervision which includes structured planning, open communication, and providing constructive feedback has a positive influence on teacher work motivation and improved performance in learning activities. In addition, the supportive and collaborative leadership style of the principal has been shown to strengthen the impact of supervision on teacher professional achievement. These findings emphasize the importance of strengthening the capacity of principals in the practice of academic supervision as a strategy to improve the quality of education.